Sex differences in olfactory cortex neuronal loss in aging - Alotaibi, Majed M.; De Marco, Matteo; Venneri, Annalena (Frontiers in Human Neuroscience, 2023)
Introduction: Ageing plays a major role in neurodegenerative disorders such as Alzheimer’s disease, and impacts neuronal loss. Olfactory dysfunction can be an early alteration heralding the presence of a neurodegenerative disorder in ageing. Studying alterations in olfaction-related brain regions might help detection of neurodegenerative diseases at an earlier stage as well as protect individuals from any danger caused by loss of sense of smell. Objectives: To assess the effect of age and sex on olfactory cortex volume in cognitively healthy participants. Method: Neurologically-healthy participants were divided in three groups based on their age: young (20–35 years; n = 53), middle-aged (36-65 years; n = 66) and older (66-85 years; n = 95). T1-weighted MRI scans acquired at 1.5 T were processed using SPM12. Smoothed images were used to extract the volume of olfactory cortex regions. Results: One-way ANOVA analyses showed significant decreases in volume between age groups in the olfactory cortex (p ≤ 0.0001). In women, neuronal loss started earlier than in men (in the 4th decade of life), while in men more substantial neuronal loss in olfactory cortex regions was detected only later in life. Conclusion: Data indicates that age related reduction in the volume of the olfactory cortex starts earlier in women than in men. The findings suggest that volume changes in olfaction-related brain regions in the ageing population deserve further attention as potential proxies of increased risk of neurodegenerative diseases.